EVALUATION OF RESULTS OF PUBLIC MUNICIPAL PASSENGER TRANSPORT WORK IN OMSK - S. M. Mochalin; M. Ev. Kasper (Вестник СибАДИ)
Introduction. The article provides the effectiveness evaluation of the municipal passenger enterprises in Omsk city, carried out according to the classification model of effectiveness indicators for passenger enterprises, which is developed by the authors. Indicators of municipal passenger enterprises in Omsk city, surveys of experts - heads of the Department of Transport and enterprises are used for adequate evaluation.Materials and methods. The set of effectiveness indicators of the enterprise (carrier) is determined by the proposed classification model. The model of indexation, the Spearman and Kendall coefficients, the coefficients of generalized and positive results are used in the article. The formalized basis is a measure of effectiveness in the form of a prioritized benchmark series of the growth indicators estimation, i.е. set of ranks of the “plan” indicators.Results. The analysis of the results of municipal enterprises is carried out in dynamics. It can be noted that with the greatest effectiveness, road transport enterprises operated in 2014, electric transport - in 2016. In 2015, most enterprises worked ineffectively, which was due to the economic situation in the region. In 2016, enterprises began to increase their efficiency, thus, there was a positive dynamic.Discussions and conclusions. The analysis of the results determined the possibility of using scientifically sound solutions as a tool for effectiveness evaluation of the passenger transport’s systems and subsystems, including passenger enterprises. Such tool allows to perform an integrated evaluation of the passenger companies’ effectiveness for a certain period and also helps to identify deviations in work process and to manage the processes in the enterprise.